Lessons learned from water-scarce cities: Proposed policies toward an integrated urban water management in Egypt - ElZein, Zeina; Abdou, Amal; Säumel, Ina (Frontiers in Water, 2022)
Water scarcity is one of the main challenges facing countries in arid or semi-arid zones. As an example, Egypt needs to deal with both insufficient quantity and quality of water for residents. Here, we propose actions and policies to promote an integrated water management approach in order to respond to water challenges in Egypt. Based on a literature review, we have selected a set of criteria concerning the environmental, economic, social, governmental, and physical dimensions of urban water management. We studied approaches from Peru, Namibia, and South Australia as these countries have similar climatic conditions and water issues and have made substantial advances towards sustainable water management. Key elements are state or municipal ownership of water and related infrastructure, agreement on master plans for sustainable water management, improvement of water sanitation and overall infrastructure, and reduction of water demand. Moreover, participatory, and educational campaigns put water issues at the center of public debates. We evaluated which elements of water management approaches can be adapted and used in Egypt, which faces limited freshwater resources and highly increasing population. Proposed actions included directing water fees to ecosystem projects, treatment of wastewater to be potable, participatory approaches that engage the community in water management, educational campaigns that lead to change of public perception and knowledge dissemination. We carried out interviews with key stakeholders in the water sector in Egypt to validate our proposed approaches. The stakeholders supported knowledge dissemination, offered suggestions to the use of water fees in implementing environmental projects and criticized treatment of wastewater into drinking water. Finally, we drafted specific recommendations at the organizational and urban levels of water management. We recommended establishing a General Organization for Water Management to oversee water-related organizations and ministries. We also recommended prioritizing the economic conditions to support alleviation of water subsidy, increasing public awareness, and creating a public database for water knowledge. In addition, we recommended decentralized water management and water sensitive urban design. The value of these approaches is their applicability, with minor adaptations, to countries with similar or close climatic and socio-economic conditions to Egypt, such as the MENA region.